(untitled) (Bangladesh Journal of Botany, 2021)
Sweet potato [Ipomoea batatas (L.) Lam.] germplasms are unique as they are heterozygous, vegitatively as well as sexually propagated and polyploid in nature. Forty-four germplasms from local farmer’s field and from various centres of India were determined using 15 RAPD and 15 ISSR markers to evaluate their genetic relatedness. Average polymorphisms for RAPD and ISSR markers were found to be 86.72 and 81.64%, respectively. The OPM series primer produced 145 total bands with 138 polymorphic loci and ISSR markers gave 116 total bands with 101 polymorphic loci. The clusters were made using the UPGMA method using both the RAPD and ISSR data and group diverse yet similar germplasm in two different clusters. This gives ample information to use them in further improvement programme.